Effectiveness of an Evidence-Based Practice Education Program for Undergraduate Nursing Students: A Systematic Review and Meta-Analysis - Jeong, Dain; Park, Chang; Sugimoto, Keiko; Jeon, Miyang; Kim, Dooyoung; Eun, Young (International journal of environmental research and public health, 2024)
This systematic review and meta-analysis examined the impact of evidence-based practice (EBP) education programs on undergraduate nursing students, focusing on enhancing EBP competency, critical thinking, and problem-solving ability. Methods: The search, conducted through PubMed, Cochrane Library, EMBASE, CINAHL, and Web of Science up to December 2023, included studies published in English and Korean and adhered to PRISMA guidelines. Qualitative appraisal of the studies was conducted using the revised ROB II for randomized trials and the ROBINS-I for non-randomized trials. For the meta-analysis, the effect size of the intervention was calculated as a standardized mean difference. Results: In our study, 11 studies met our inclusion criteria, and 8 studies of those were included in the meta-analysis. The effect sizes for EBP competency, critical thinking, and problem-solving ability were 1.55, 1.29, and 0.65, respectively. The meta-regression analysis indicated that tailored education programs of 4–7 weeks and being in the 4th grade significantly enhanced EBP competency. Conclusion: These findings support the development of a customizable and applied EBP education actively for students, preparing nursing students to effectively implement EBP in clinical settings after graduation. Despite the significant effect size of the outcome variables, the high heterogeneity suggests the need for further investigation to validate the EBP educational outcomes for nursing students.